PENGARUH FAKTOR DEMOGRAFI DAN ATRIBUT RITEL TERHADAP FREKUENSI BELANJA KONSUMEN ELEKTRONIK DI SURABAYA - SALIM, SWIJIANA (JURNAL ILMIAH MAHASISWA MANAJEMEN, 2012)
The purpose of the research is to examine the influence of factors of demography, and retail attributes on the shopping frequency at elektronic stores. The sample of respondents totals 103 people and the data collected are analyzed using the multiple linear regression. The result shows that the demography variable doesn’t have any significant effect on the dependent variable whereas the other independent variable does